MHD flow and heat transfer of Cu–water nanofluid in a semi porous channel with stretching walls - Raza, Jawad; Mohd Rohni, Azizah; Omar, Zurni (Elsevier Ltd., 2016)
This paper deals with heat transfer analysis on MHD nanofluids in a porous channel with stretching walls. An incompressible Copper (Cu)–water nanofluid is filled in the porous channel. The governing partial differential equations are first transformed into ordinary differential equations by using suitable similarity transformation. The resulting nonlinear ordinary differential equations are then solved numerically by using shooting method. It is found that the different values of nanoparticle volume fraction, Reynolds number, magnetic field and Prandtl number affects the profiles of velocity, temperature, skin friction and heat transfer.